Gut hormones in acute diarrhoea. Issue 7 (July 1983) - Besterman, H S; Christofides, N D; Welsby, P D; Adrian, T E; Sarson, D L; Bloom, S R
Abstract : The gut hormone response to a breakfast meal was studied in 12 subjects hospitalised for an episode of acute diarrhoea (presumed infective) who were otherwise well and in 13 healthy control subjects. Fasting blood glucose concentrations were low but basal insulin concentrations were raised. Basal concentrations of pancreatic polypeptide and both basal and postprandial responses of motilin, enteroglucagon, and vasoactive intestinal polypeptide (VIP) were also significantly greater than controls. No abnormalities in plasma concentrations of gastrin, gastric inhibitory polypeptide (GIP) or pancreatic glucagon were found. The suggested physiological actions of the raised hormones may be relevant to the pathophysiology of diarrhoea.